Does the 9p region affect arterial stiffness? Results from a cohort of hypertensive individuals. (October 2013) - Cesana, Francesca; Nava, Stefano; Menni, Cristina; Boffi, Lucia; Varrenti, Marisa; Meani, Paolo; Maloberti, Alessandro; Grassi, Guido; Giannattasio, Cristina; Mancia, Giuseppe
Abstract Objective. Evidence exists that arterial stiffness, i.e. an independent predictor of cardiovascular and all-causes mortality, has a genetic component. The 9p21 region is associated with a greater susceptibility to coronary disease. Whether this can be ascribed to the fact that genes located on chromosome 9p may also regulate arterial stiffness is largely unknown, however. We evaluate the influence of single nucleotide polymorphisms (SNPs) from 9p on carotid–femoral pulse wave velocity (C-F PWV), measured via the Complior method, in a cohort of 821 hypertensive subjects. Design. The selected tagSNPs were screened with a custom-designed 384-plex VeraCode GoldenGate Genotyping assay on Illumina BeadXpress Reader platform. Association analysis was done using PLINK considering C-F PWV as a quantitative trait (linear regression assuming an additive model) adjusting for sex, age, systolic blood pressure and body mass index (BMI). We used false discovery rate (FDR) to account for multiple testing. Results. Although none of the 384 SNPs was significant after adjusting for multiple testing, probably due to the small sample size of the study population, a trend of association with C-F PWV was observed for rs300622 and rs2381640. Conclusions. These data suggest that SNPs located on chromosome 9p may affect arterial stiffness. Further studies are needed to confirm our finding on a larger sample and define the physiopathological link of the present results.